Del Compromiso Presencial al Virtual: Adaptaciones de un Proceso Participativo para el Diseño de una Política Pública de Basura Marina en Brasil - Elliff, Carla; de Andrade, Mariana; Grilli, Natalia; Scrich, Vitória; Panarelli, Ana Maria; Neves, Ana Maria; Romanelli, Maria Fernanda; Mansor, Maria Teresa; Cardoso, Omar; Zanetti, Rita; Turra, Alexander (Costas, 2022)
Marine litter is a transversal issue that affects the envi- ronment and society in a multitude of ways. As such, solutions to this problem are complex and demand the engagement of multiple sectors of society. The São Paulo Strategic Plan for Monitoring and Assessment of Marine Litter (PEMALM) is the first public policy of its kind, seeking to establish indicators and build knowledge to move towards a plan to combat marine litter in the most populous state in Brazil. From its inception, PEMALM has sought to establish a participative construction frame- work, involving key stakeholders at each step. When the Covid-19 pandemic struck, the participative construction process had to be adapted. Here we present and discuss the strategies applied in the participatory process of PEMALM to guarantee the remote engagement of stakeholders. Three participatory milestones were part of the final policy-making process: a first in-person workshop which gathered stakeholders in a single location, a series of in-person meetings in which the project team travelled to where the stake- holders are located, and, due to the Covid-19 pandemic, an entirely virtual workshop. Sector participation was found to be alike for online and on-site events, with higher participation of the public sector, followed by academia, NGOs and the private sector in both. The adjustments and the adaptive effort placed on the participatory process due to the Covid-19 pandemic, such as being dedicated and attentive to the needs of attendees, expanding the modes of interaction and promoting a flexible and light schedule to reduce online fatigue, guaranteed the quality of stakeholder engagement and participation. The positive accomplishments of the hybrid strategy used in building PEMALM as a public policy exemplifies ways to facilitate and broaden participation in the co-construction under mobility restrictions.